OpenStudy (anonymous):

Can someone help me with this question? I'm stuck. I'll fan/medal and whatnot. The work of a student trying to solve the equation 4(2x − 1) = 11 + 3x + 5 is shown below: Step 1: 4(2x − 1) = 11 + 3x + 5 Step 2: 8x − 4 = 16 + 3x Step 3: 8x + 3x = 16 − 4 Step 4: 11x = 24 Step 5: x = 2.18 In which step did the student first make an error and what is the correct step? A. Step 2: 8x − 1 = 16 + 3x B. Step 2: 8x − 8 = 6 + 3x C. Step 3: 8x − 3x = 16 + 4 D. Step 3: 8x + 3x = 16 − 8

3 years ago
OpenStudy (sepeario):

C.

3 years ago
OpenStudy (sepeario):

You are meant to subtract 3x from both sides of the equation, not add. The same goes with 4. You are meant to add the 4 from both sides, not subtract.

3 years ago
OpenStudy (anonymous):

Thank you very much

3 years ago
OpenStudy (sepeario):

would you mind medalling me ^^ :) it was my pleasure.

3 years ago